Analisis Reputasi Merek Dan Kualitas Produk Terhadap Keputusan Pembelian - Rifki Ramdhan; Kokom Komariah; Dicky Jhoansyah (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Based on the results of the study it was found that purchasing decisions had decreased, which was seen from the data on the best-selling laptop brands in 2020, where the Lenovo laptop brand was ranked 4th, only obtaining an assessment index of 10.3%. This study aims to determine the effect of brand reputation and product quality on purchasing decisions at the Muhammadiyah University of Sukabumi. The method used in this research is descriptive and associative with a quantitative approach. The data collection method uses a questionnaire, which is then analyzed using multiple regression with the classical assumption test. The sampling technique in this study used a probability sampling technique, the samples used in this study were 100 student respondents at the Muhammadiyah University of Sukabumi. The results of this study show that there is a simultaneous relationship between the variables Brand Reputation and Product Quality on Purchasing Decisions with the results F count 113.458 > F table 3.089 and the T-Test test shows that the brand reputation variable on purchasing decisions has an insignificant positive effect, while the variable Product quality has a positive and significant effect on purchasing decisions. Keywords: Brand Reputation, Product Quality, Purchase Decision